Communication effectiveness of counselling teacher on career maturity of Vocational High School (SMK) students - Virginia, Prima; Lindawati, Sri (Privietlab, 2025)
The age of SMK students falls into the category of adolescents who tend to need guidance and direction, especially in the school environment, namely career assistance that can be provided by Counselling Guidance (BK) teachers. Many adolescents tend to spend more time with their peers than with their teachers and parents. This research examines the effectiveness of interpersonal communication between counselling teachers and vocational students towards career maturity in terms of communication effectiveness in the form of openness, positive attitude, support, equality, and empathy. Career maturity consists of the elements of concern, curiosity, confidence, and consultation. This research uses a mixed method that combines quantitative and qualitative methods with the help of descriptive, correlation, and regression tests, as well as in-depth analysis through interviews and observations. The results showed that the communication intervention of counselling teachers was more effective in increasing vocational school students’ career maturity.